Split Tibialis Anterior Tendon Transfer to The Peroneus Brevis or Tertius for the Treatment of Varus Foot Deformities in Children with Static Encephalopathy: A retrospective case series. (May 2020) - Lullo, Brett; Nazareth, Alexander; Rethlefsen, Susan; Illingworth, Kenneth D.; Abousamra, Oussama; Kay, Robert M.
Abstract : Introduction: The study purpose was to determine the safety/efficacy of a split anterior tibialis tendon transfer (SPLATT) to the peroneus tertius or brevis in children with static encephalopathy and varus feet. Methods: A retrospective review of short- and long-term complications, change in ankle range of motion, strength, and gait kinematics. Predictors of postoperative varus or valgus were examined. Results: One hundred thirty-three patients were included (average age [SD] 10.3 [3.7]), with an average follow-up of 3.9 (3.4) years. Forefoot/hindfoot eversion range of motion improved ( P ⩽ 0.05), dorsiflexor strength was maintained or improved in 76.9% of patients, and dorsiflexion in swing phase was maintained. Complications occurred in 6 of 133 patients (4.5%) and included 1 transfer failure, 1 wound dehiscence, and four pressure areas from casts. Successful correction was achieved in 77% of patients. Later onset of recurrent varus (14.4%, 10.6% requiring revision surgery) and pes valgus (8.7%, 4.8% requiring revision surgery) occurred. The length of the follow-up predicted the development of the pes valgus (odds ratio 1.28, 95% CI 1.0 to 1.6). Discussion: SPLATT to the peroneus tertius or brevis is effective, and complications are rare. Subsequent valgus or recurrent varus deformities may occur, possibly requiring repeat surgery.